Paz Encina: Voces en la oscuridad - Eduardo A. Russo (Caravelle)
This paper examines Paz Encina’s work in the re-elaboration of historical memory concerning the State repression in Paraguay, based upon her researches in the Terror Archive. From her own treatment of these data, this artist developped an audio-visual creation mode particularly determined by sound, and above all the human voice and its presence effects in relation to missing bodies.